Herpes zoster incidence and burden in older Chinese: a systematic review and meta-analysis - Bingbing Zheng; Dapeng Yin; Yifan Geng; Qiao Li; Wenting Cao; Mingzhang Yin; Yi Ning; Jindong Ding Petersen (BMC Public Health)
Abstract Background Previous studies have documented variations in herpes zoster (HZ) incidence across regions and periods. We aimed to synthesize data on HZ incidence, complications, and associated healthcare costs (inpatient and outpatient) in the Chinese population aged 50 years and older over the last two decades. Methods We searched studies published in English between January 1, 2000, and March 31, 2023 in PubMed, Cochrane Library, Embase, EBSCO, OVID, and Web of Science, supplemented by Chinese databases CNKI, Wan Fang, CQVIP, and Yiigle. Main search terms included ‘Herpes Zoster’, ‘Herpesvirus 3, Human’, ‘Neuralgia Postherpetic’, ‘incidence’, ‘morbidity’, ‘epidemiology’, ‘complication’, ‘health care cost’, ‘expenditure’, ‘economic’, and ‘burden’. The Agency for Healthcare Research and Quality tool and Newcastle-Ottawa Scale were used for quality assessment. Results Of 6,958 studies, 19 (73,044,981 total population) were included for analysis (1,107,682 HZ cases, mean age 63.03 ± 8.30 years, 47.10% male). The pooled annual HZ incidence from 13 studies (2 with high quality, 11 with medium quality) from 2000 to 2020 was 6.28 per 1000 PYs (95%CI: 5.42, 7.15), with a significant increasing trend over the period (meta-regression coefficient: 0.0031, 95%CI: 0.0027, 0.0036), and more pronounced among females and those with advancing age. Neuralgia system disorders were the most frequently reported complications, followed by ear and eye diseases. Furthermore, HZ-associated inpatient costs showed a 4.4-fold dramatic increases, rising from 3260 RMB in 2010–2012 to 14,303 RMB per patient in 2017–2018, while outpatient costs remained growth from 336 RMB to 1329 RMB. Conclusions Despite the medium overall quality of the studies, our findings highlight an urgent need for effective public health strategies including vaccine aimed at reducing HZ incidence and associated healthcare costs in China.